ANTARA MITOS ”UNGKU SALIAH” DENGAN “HAJI SALEH MASUK NERAKA”: MAKNA, KONSEP KATA “SALEH” PENDEKATAN SEMIOTIK BUDAYA - Sulastri Sulastri (Jurnal Sosioteknologi, 2009)
The meaning and concept of the word “saleh” is unique in literary studies. There are many interpretations of “saleh” in the short story “Robohnya Surau Kami” written by Navis. The meaning and concept can be comprehensively analyzed by using many approaches, one of which is by Cultural Semiotics approach. This study shows a process of signification and extension of meaning and concept as a very dynamic metalanguage.